PRODUCTIVE AND ECONOMIC RESPONSE OF GUINEA PIGS TO THE USE OF FOUR TYPES OF FORAGE FEEDERS - Sánchez V., Raúl (2013)
The study evaluated the effect of various types of forage feeders on the efficiency offorage usage and on the productive and economic response of guinea pig (Caviaporcellus) breeding. A total of 250 weaned male of 15 days of age at the Mantaro valley,Junín, Peru were used in a completely randomized design with five treatments of foragesupply and five repetitions per treatment. Each repetition corresponded to a cage withten guinea pigs. Four forage feeders were evaluated: cylindrical mesh on the floor (CMP),hanging U shaped mesh (MCU), iron grilled with foot on the floor (PFP) and hopper meshin V shaped (TMV), plus the traditional method with the forage directly on the floor(DSP). The use of feeders improved forage consumption efficiency, total food consumptionand benefit cost ratio (p<0.05). MCU was the most promising feeder in terms of forageconsumption efficiency, body weight gain, total feed consumption, unit production costand benefit cost ratio (p<0.05). It is concluded that the use of feeders improves productiveand economic parameters, and the best feeder was the hanging U shaped mesh (MCU).